A Phenomenological Study of Parental Emotional Acceptance of Children with Hearing Disabilities in Indonesia - Wilian, Yurisa Ilham; Paningit, Mahalia Putri; Fatira, Anggun Zahra; Mahadur, Grace Natasia; Sholihah, Kholifah Umi (Pedagogi : Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to examine how parents of children with hearing disabilities in Indonesia experience and construct emotional acceptance, with particular attention to the subjective meanings and emotional dynamics following their child’s diagnosis, as interpreted through an Interpretative Phenomenological Analysis (IPA) framework. This research employed a qualitative design using Interpretative Phenomenological Analysis. Data were collected through in-depth, semi-structured interviews and non-participant observations involving three parents of children with hearing disabilities enrolled at a public special education school (SLBN) in Central Java, Indonesia. The study focused on capturing parents’ lived experiences and meaning-making processes. Data analysis followed systematic IPA procedures, including idiographic analysis and cross-case interpretation, supported by triangulation and member checking to enhance credibility. The findings reveal that parents experience emotional acceptance through dynamic and fluctuating processes that resemble the stages of denial, anger, bargaining, depression, and acceptance as proposed by Kübler-Ross. However, these stages do not emerge in a linear sequence. Instead, parents’ emotional experiences shift depending on psychological conditions, interpersonal relationships, spiritual beliefs, and access to emotional support. Denial functions as an initial protective mechanism, anger reflects feelings of helplessness and loss of control, bargaining represents attempts to preserve hope, and depression manifests as emotional exhaustion and social withdrawal. Acceptance develops as parents reconstruct meanings of disability and parenthood, demonstrated through adaptive actions such as learning sign language and redefining expectations for their child’s development. This study contributes theoretically by demonstrating that emotional acceptance among parents of children with hearing disabilities is an ongoing, interpretative, and non-linear meaning-making process rather than a fixed emotional trajectory.